PENGARUH REKRUTMEN DAN PELATIHAN KERJA TERHADAP KINERJA KARYAWAN PADA PT ZIBEN INDONESIA BOGOR - Submission JORAPI; Yatulus Gulo; Arief Budi Santoso (Journal of Research and Publication Innovation, 2024)
The aim of the research is to determine and analyze the effect of recruitment on employee performance, the effect of training on employee performance. As well as to determine the effect of recruitment and training together on the employee performance of PT Ziben Indonesia Bogor. The population and sample in this research were employees at PT Ziben Indonesia Bogor, totaling 102 samples using a saturated sampling technique. The research method used is a quantitative descriptive method, collecting data by distributing questionnaires which are then processed using regression analysis. The tests used to test research instruments are validity and reliability tests, classic assumption tests, namely: Normality test, multicollinearity test, and autocorrelation test. Meanwhile, hypothesis testing consists of: correlation test, determination test, regression test, t test (partial) and F test (simultaneous) with the help of SPSS 24 for Windows software. The results of the t statistical test analysis for the Recruitment variable have a calculated t value of 3.886 > t table 1.664 with a significance value of 0.000 < 0.05, the Training variable has a calculated t value of 3.147 > t table 1.664 with a significant value of 0.002 < 0.05. The correlation value is 0.881 or with a very strong interpretation and the determination value is 77.6%. From the results of the F statistical test (simultaneous), it can be seen that the F-count value is 171.008 > F-table 3.09 and the significant value is 0.000 < 0.05, so it can be concluded that Recruitment and Training have an influence on Employee Performance.